Phospholipase A2 as a novel therapeutic target in lung cancer. Issue 6 (December 2020) - Zhang, Fang-Yuan; Li, Run-Ze; Li, Jia-Xin; Fan, Xing-Xing; Xie, Chun-; Liu, Liang; Yao, Xiao-Jun; Leung, Elaine Lai-Han
No abstract available